Examining the role of workplace spirituality in achieving job satisfaction: a study on Pakistani doctors - Anjum, Zara (070019) 2013 (Islamabad Department of Business Administration (Air University Main Campus), 2013)
This study aims at identifying the relationship existing between the dependent variable that is Job Satisfaction and the independent variable, Workplace Spirituality. A sample of 80 doctors working in Private and public hospitals was targeted. Of the five independent variables; Team Sense of Community, Alignment between organizational and individual values, Sense of contribution to the community, Sense of enjoyment at work and Opportunities for inner life four variables were found to be significant. Four hypotheses were accepted; Team$1 (Bs sense of community, Sense of Contribution, Alignment between organizational and individual values and Sense of Enjoyment at work has an effect on job satisfaction. Sense of community contributed 23.5%, Alignment contributed 20%, contribution to the community contributed 21.2%, while enjoyment contributed 81.1% to the model in describing Job Satisfaction. Future studies can include moderating and mediating variables in this model of Workplace Spirituality that can support and benefit the outcomes of this result.s
BBA